2020
DOI: 10.1101/2020.08.21.20166355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio (PLR), a novel biomarker to predict the severity of COVID-19 patients: a systematic review and meta-analysis

Abstract: Background Platelet-to-lymphocyte ratio (PLR), a novel inflammatory marker, has been suggested to be able to predict the severity of COVID-19 patients. This systematic review aims to evaluate the association between PLR levels on admission and the severity of COVID-19 patients. Methods A systematic literature search was done on 23 July 2020 to identify peer-reviewed studies across four different databases (Ovid MEDLINE, EMBASE, SCOPUS, and the Cochrane Library), preprints from two databases (MedRxiv and SSRN),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The findings of the present study were similar to the study done by Simadibrata DM et al, which showed that the patients with severe COVID-19 illness had higher PLR levels on admission (SMD 0.68; 95%CI 0.43-0.93; I2 =58%) [7].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study were similar to the study done by Simadibrata DM et al, which showed that the patients with severe COVID-19 illness had higher PLR levels on admission (SMD 0.68; 95%CI 0.43-0.93; I2 =58%) [7].…”
Section: Discussionsupporting
confidence: 92%
“…Platelet-to-lymphocyte ratio is another simple costeffective but less commonly used method that is calculated from CBC and could be of a value in predicting COVID-19 severity. Two recent meta-analysis evaluating PLR value in COVID-19 infection showed that cases with severe COVID-19 had higher admission levels of PLR [29,30]. Moreover, the number and the dynamic fluctuations of the platelets during the management may provide an idea on the prognosis and severity of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Upsurge in the PLR meter recommend an overactive inflammatory reaction and worsen prognosis. Additionally, PLR is sensitive towards natural as well as acquired immune reactions [3,8,9]. The normal range of the PLR is varied and based on several clinical research.…”
Section: Introductionmentioning
confidence: 99%